Long-term impact of Covid-19: psychological disturbances and cognitive functioning of recovered professionals in Dhaka - Baroi, Bijon; Muhammad, Noor; Himi, Samsad Afrin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Hospitalization or home isolation may have an acute effect on the mental health and cognitive functioning of COVID-19 recovered professionals, but there is a lack of studies in this regard. This cross-sectional study examined the possible psychological disturbances and impairment in cognitive functioning among COVID-19 recovered professionals in Bangladesh. A total of 118 COVID-19 recovered professionals participated in an online survey, in which they completed a questionnaire including personal and pandemic-specific questions, as well as measures of psychological disturbances and cognitive failure. Results revealed that only onefifth of professionals experienced psychological disturbances, but half of the people had severe impairment in cognitive functioning. The low rate of psychological distress may reflect the resilience of Bangladeshi people due to our collectivistic society. In contrast, the relatively high prevalence of subjective cognitive impairment would imply that prolonged quarantine/selfisolation was at least partially responsible for a perception of reduced cognitive efficiency. The findings, however, highlight the importance of developing intervention programs to improve the psychological well-being and cognitive functioning of professionals during pandemics.